Waga rzeźnikiem. Co w tym śmiesznego? Astrologiczny humor w Uczcie Trymalchiona Petroniusza - Krogulska, Miłosława (Colloquia Litteraria, 2024)
The astrological references in Petronius’ Cena Trimalchionis (Trimalchio’ Dinner) serve an important function in establishing the comic mood. They appear as a theme in the menu, are used in a humorous way to describe human characters, and contribute to the suspense of the final scene. A critical examination of the astrological descriptions reveals inconsistencies with the ancient astrological system. This may indicate that the author intentionally used this stylistic device to create the impression of a broken and damaged world.